Serum Protein and Cholesterol Levels in Kankrej Heifers at various reproductive stages in different feeding regimes - AMBATKAR, S V; RADADIA, N S; PANDEY, S K; NINAN, J; VADODARIA, V P (The Indian Journal of Animal Reproduction, 2023)
Changes in the Total Serum Protein (TSP) and Total Serum Cholesterol (TSC) levels were noted in 18 pregnant heifers, divided into three groups as per their feeding regimes, both at prepartum and postpartum periods. TSP and TSC levels varied significant (P < 0.01) with respect to various reproductive stages. However, their levels were almost same at any reproductive stage under the three feeding regimes undertaken, indicating that even low cost feeding was equally capable of maintaining normal levels at par with the other groups.
Keywords: serum protein; kankrej Heifers